Methanol Extract and Nanocomposite of Trichoderma sp as a Potential Bio-Control against Fusarium moniliforme in Tomato (Lycopersicon esculentum) - Inovejas, R. C.; Divina, C. C. (International Journal of Agricultural Technology, 2018)
Nanotechnology has been cited as the foundation of a new advanced agriculture. It is a rapidly developing domain of research and practice. The potential uses and benefits of nanotechnology are enormous. These include plant disease management through the formulation of nanomaterials-based products. Use of pesticides and fungicides has been found to be effective against different plant pathogens but the large use of these chemicals can lead to serious problems, including environmental pollution and human health hazards. Therefore, alternative strategies are being widely employed. One potential strategy to counter attack pathogen is the use of bio-control agents. Trichoderma sp. is widely studied bio-control agent against plant pathogens because of their ability to reduce the population of soil borne plant pathogens including Fusarium sp. that causes wilt in tomato. The study determined the effectiveness of methanol extract and nanocomposite of Trichoderma sp. as a potential bio-control against Fusarium moniliforme in tomato through in- vitro and in- vivo conditions. In-vitro assays conducted were bi-culture and slide bi-culture while in-vivo assay was done using modified leaf assay. In-vitro results revealed that Trichoderma sp. colonized F. moniliforme and suppressed the growth by an average of 2.84 cm which resulted to damaged and deformed hyphae. In-vivo results showed that the methanol extract of Trichoderma sp. reduced the disease incidence and severity, while the nanoTrichoderma extract did not. Given the results, it can be concluded that Trichoderma sp. had antagonistic property in controlling growth of Fusarium moniliforme.